Clinical-Pharmacogenetic Predictive Models for Time to Occurrence of Levodopa Related Motor Complications in Parkinson’s Disease - Redenšek, Sara; Jenko Bizjan, Barbara; Trošt, Maja; Dolžan, Vita (Frontiers in Genetics, 2019)
The response to dopaminergic treatments in Parkinson's disease depends on many clinical and genetic factors. The very common motor fluctuations and dyskinesia affect approximately half of patients after five years of treatment with levodopa. We did an evaluation of a combined effect of 16 clinical parameters and 34 single nucleotide polymorphisms to build clinical and clinical-pharmacogenetic models for prediction of time of occurrence of motor complications and to compare their predictive abilities. In total, 220 Parkinson's disease patients were included in the analysis. Their demographic, clinical, and genotype data were obtained. The combined effect of clinical and genetic factors was assessed using The Least Absolute Shrinkage and Selection Operator penalized regression in the Cox proportional hazards model. Clinical and clinical-pharmacogenetic models were constructed. The predictive capacity of the models was evaluated with the cross-validated area under time-dependent receiver operating characteristic curve. Clinical-pharmacogenetic model included age at diagnosis (HR=0.99), time from diagnosis to initiation of levodopa treatment (HR=1.24), COMT rs165815 (HR=0.90), DRD3 rs6280 (HR=1.03), and BIRC5 rs9904341 (HR=0.95) as predictive factors for time to occurrence of motor fluctuations. Furthermore, clinical-pharmacogenetic model for prediction of time to occurrence of dyskinesia included female sex (HR=1.07), age at diagnosis (HR=0.97), tremor-predominant Parkinson’s disease (HR=0.88), beta-blockers (HR=0.95), alcohol consumption (HR=0.99), time from diagnosis to initiation of levodopa treatment (HR=1.15), CAT rs1001179 (HR=1.27), SOD2 rs4880 (HR=0.95), NOS1 rs2293054 (HR=0.99), COMT rs165815 (HR=0.92), and SLC22A1 rs628031 (HR=0.80). Areas under the curves for clinical and clinical-pharmacogenetic models for motor fluctuations after five years of levodopa treatment were 0.68 and 0.70, respectively. Areas under the curves for clinical and clinical-pharmacogenetic models for dyskinesia after five years of levodopa treatment were 0.71 and 0.68, respectively. These results show that clinical-pharmacogenetic models do not have better ability to predict time of occurrence of motor complications in comparison to the clinical ones despite the significance of several polymorphisms. Models could be improved by a larger sample size and by additional polymorphisms, epigenetic predictors or serum biomarkers